Audit Evidence Sufficiency and Auditor Opinion Formation Processes (gjstudies, 2018)
This research introduces a novel, cross-disciplinary framework for conceptualizing audit evidence sufficiency and the cognitive processes underlying auditor opinion formation.Moving beyond traditional quantitative and checklist-based approaches prevalent in auditingliterature prior to 2005, this paper applies principles from complex systems theory, cognitivepsychology, and information foraging theory—domains not previously synthesized in this context. We propose that evidence sufficiency is not a static threshold but a dynamic, contextdependent equilibrium point influenced by cognitive load, environmental uncertainty, andthe auditor’s internal mental model of the audit space. The methodology employs a hybridqualitative-quantitative design, utilizing a series of controlled simulation experiments withpracticing auditors, coupled with protocol analysis of their verbalized reasoning. Our findingsreveal three previously unidentified heuristics—’narrative coherence seeking,’ ’contradictiontolerance thresholding,’ and ’evidence source topology mapping’—that significantly influencesufficiency judgments in ways not predicted by existing standards or models. Furthermore,the results demonstrate that auditors often reach a subjective state of ’cognitive sufficiency’well before traditional evidential benchmarks are met, a phenomenon we term ’prematureepistemic closure.’ This has profound implications for audit quality and the detection ofmaterial misstatement. The paper concludes by arguing for a paradigm shift from evidence*accumulation* to evidence *integration* models in auditing standards and practice, offering a new theoretical lens and practical toolkit for enhancing the rigor and reliability of theaudit opinion process.